Atopy patch test in the diagnosis of food allergy in children with atopic dermatitis - Jesenák, Milos; Bánovcin, Peter (Acta medica (Hradec Kralove), 2006)
Atopic eczema/dermatitis syndrome (AEDS) is one of the most common chronic allergic diseases in children. Among the allergens found to be relevant in AEDS, aeroallergens and food allergens are the most important. The exposure of these patients to their relevant protein allergens can trigger an exacerbation or maintain the disease. AEDS is frequently associated with food allergy, which complicates the management in approximately 40% of these children. Atopy patch test (APT) can help in detecting food allergies in children with AEDS. The earliest publication on patch testing in eczema was described in 1937 by Rostenberg, but the first controlled clinical trial was provided by Mitchell in 1982. APT with food allergens were introduced into clinical use in 1996 by the group of Isolauri. APT test is performed epicutaneously with typical immediate-type allergens (aeroallergens or foods). As a number of apparently minor test modifications greatly influence the sensitivity, specificity, and reproducibility of the APT, the European Task Force on Atopic Dermatitis (ETFAD) has developed a standardized APT technique. APT has developed into a valuable additional tool in the diagnostic work-up of food allergy in infants and children with atopic dermatitis.
Keywords: Child; atopická dermatitida; Patch Tests; dítě; Food Hypersensitivity; lidé; Dermatitis, Atopic; náplasťové testy; Humans; potravinová alergie